2008
DOI: 10.1517/14656566.9.5.751
|View full text |Cite
|
Sign up to set email alerts
|

Costs, quality of life and treatment compliance associated with antibiotic therapies in patients with cystic fibrosis: a review of the literature

Abstract: Evidence suggests that inhaled tobramycin, a key chronic suppressive therapy, can reduce other healthcare costs. The main determinants of the cost of care include disease severity and respiratory infection. Costs vary widely by country. There is evidence that inhaled tobramycin and oral azithromycin improve quality of life and that treatment setting and patient convenience may also impact on quality of life. Antibiotic treatment compliance varied significantly and depended on the method of measurement, with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 54 publications
2
26
0
7
Order By: Relevance
“…Indeed, compared with a previous review of randomized controlled trials examining adherence rates for airway clearance techniques (88 -96%), 14 rates for compliance in observational studies reported in the present study are lower (33.3-91.2%). The previous review of adherence to antibiotics (mixed methodologies) reported similar adherence rates (35-87%) 13 compared with the present review (36 -85%).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, compared with a previous review of randomized controlled trials examining adherence rates for airway clearance techniques (88 -96%), 14 rates for compliance in observational studies reported in the present study are lower (33.3-91.2%). The previous review of adherence to antibiotics (mixed methodologies) reported similar adherence rates (35-87%) 13 compared with the present review (36 -85%).…”
Section: Discussionsupporting
confidence: 82%
“…Adherence rates have been reported to be 67% for oral antibiotics, 31-53% for inhaled antibiotics, 7 33% for dornase alfa, and 40 -70% for chest physical therapy. 3,[8][9][10][11][12] Although adherence levels for subcategories of 2 of the 4 WHO recommendations have been the subject of systematic reviews (adherence to antibiotics only, 13 airway clearance techniques 14 ), the inclusion of randomized controlled trials may not reflect participants' level of adherence to their independent home treatment regimes due to the nature of frequent monitoring as part of being involved in a trial. Hence, this review was undertaken to include all 4 WHO recommendations (nutrition, medication, exercise, pancreatic enzyme replacement therapy) in non-interventional studies.…”
Section: Introductionmentioning
confidence: 99%
“…These data are confirmed by other researchers in other medical fields. For example, it was determined that the lack of readiness to cooperate and oppositional behaviours have a negative effect on adherence to treatment also in patients with cystic fibrosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Weiner et al, 251 from Boston, carried out a literature review examining costs, QoL and compliance with treatment. The cost data are useful and are referred to elsewhere.…”
Section: Medline = 1064 Retrieved Embase = 1281 Retrievedmentioning
confidence: 99%